The Impact of Psychiatric Patient Boarding in Emergency Departments - B. A. Nicks; D. M. Manthey (Emergency Medicine International)
Objectives. Studies have demonstrated the adverse effects of emergency department (ED) boarding. This study examines the impact of resource utilization, throughput, and financial impact for psychiatric patients awaiting inpatient placement. Methods. The authors retrospectively studied all psychiatric and non-psychiatric adult admissions in an Academic Medical Center ED (>68,000 adult visits) from January 2007-2008. The main outcomes were ED length of stay (LOS) and associated reimbursement. Results. 1,438 patients were consulted to psychiatry with 505 (35.1%) requiring inpatient psychiatric care management. The mean psychiatric patient age was 42.5 years (SD 13.1 years), with 2.7 times more women than men. ED LOS was significantly longer for psychiatric admissions (1089 min, CI (1039–1140) versus 340 min, CI (304–375); 𝑃<0.001) when compared to non-psychiatric admissions. The financial impact of psychiatric boarding accounted for a direct loss of ($1,198) compared to non-psychiatric admissions. Factoring the loss of bed turnover for waiting patients and opportunity cost due to loss of those patients, psychiatric patient boarding cost the department $2,264 per patient. Conclusions. Psychiatric patients awaiting inpatient placement remain in the ED 3.2 times longer than non-psychiatric patients, preventing 2.2 bed turnovers (additional patients) per psychiatric patient, and decreasing financial revenue.